Other voices? The state of public relations history and historiography: Questions, challenges and limitations of 'national' histories and historiographies. (January 2017) - Fitch, Kate; L'Etang, Jacquie
This essay offers an overview of public relations history and historiography, using a review of a recently published book series as a starting point. In offering sometimes previously undocumented national histories and regional and non-US perspectives, National Perspectives on the Development of Public Relations: Other Voices opens up the field. However, the series also raises philosophical and methodological issues regarding the role of history, the positioning of public relations, tensions within the field and public relations' relationship to societal communication and powerful strategic interests. Scholars have not always grounded their histories within wider historical literature that contextualises the public relations occupation and its role in a particular societal context. We argue that a renewed focus on historiography is needed to better address the influence of US progressivist accounts, the scientisation of western public relations and the narrow confines of the public relations discipline.